Mac OSX productivity tips for developers - Berglund, Tim (O'Reilly Media, 2013)
"Want to keep better track of information, manage your open applications, make working with the terminal more productive, recall information quickly, manage files rapidly, and produce documentation in a portable and effective manner? This video course shows you how to apply a wide range of tools and techniques - including shell enhancements, markdown files, spotlight filters, and more - to help you become a more productive developer on the Mac OS X platform."--Resource description page.